3 - Modelling an African Research University: Notes towards an Interdisciplinary, Cross-Cultural and Anticipative Curriculum - Mavhunga, Clapperton Chakanetsa (Journal of Higher Education in Africa, 2022)
What kind of education do we want our students to have in order to meet the opportunities and challenges facing Africa? What kind of ingredients and tools does such an education require to be responsive to the needs of all of Africa’s people? Mobilising around engineering education and its synergies with entrepreneurial education, vocational education, and the social sciences and humanities, this essay argues for an interdisciplinary, cross-cultural and anticipative curriculum that emphasises research, problematising and problem-solving. The article is organised around five potential ingredients a research university could prioritise: research capability, not just capacity; financial means to do research; partnership with society (the informal economy); entrepreneurship; and an interdisciplinary, cross-cultural ethos that addresses current and anticipates future challenges.